2021
DOI: 10.1111/are.15299
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis spores as an adjuvant to enhance the protection efficacy of the SVCV subunit vaccine (SVCV‐M protein) in German mirror carp ( Cyprirnus Carpio Songpa Linnaeus Mirror )

Abstract: Spring viraemia of carp (SVC) is an acute infectious disease caused by the spring viraemia of carp virus (SVCV). As a well-known disease of aquatic animals that is recognized by the International Office of Epizootics, SVC has the characteristics of high infectivity and high mortality (Ahne et al., 2002;Embregts et al., 2017;Teng et al., 2007).Cyprinids, including zebrafish (Danio rerio), silver carp (Hypophthal michthys molitri x), gold fish (Carassius auratus), catfish (Silurus glanis) and grass carp (Ctenoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The mortality of orally vaccinated European seabass was reduced from 40% to 13%. The previously reported adjuvant properties of B. subtilis spores ( 45 , 72 , 73 , 99 ) together with the immunomodulatory capacity of their metabolites ( 40 , 102 ) might have contributed to the protection observed ( 14 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The mortality of orally vaccinated European seabass was reduced from 40% to 13%. The previously reported adjuvant properties of B. subtilis spores ( 45 , 72 , 73 , 99 ) together with the immunomodulatory capacity of their metabolites ( 40 , 102 ) might have contributed to the protection observed ( 14 ).…”
Section: Discussionmentioning
confidence: 91%
“…Further, survival of unvaccinated larvae or larvae "vaccinated" with spores of the WT parental strain (not carrying the CotY-OmpK) was not significantly different from each other, indicating that it was the antigen and not the spore itself responsible for the increased protection observed. Nevertheless, an adjuvant contribution of the spores cannot be ruled out, as it has been previously described both in mammals and in fish (45,72,73,99).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Peptidoglycans acting on bacterial walls promote hydrolysis of the link between n-acetyl- d -glucosamine and n-acetyluric acid and play a role in mediating resistance to microbial invasion [ 44 ]. Examples include Cyprirnus Carpio Songpa Linnaeus Mirror [ 45 ], olive flounder ( Paralichthys olivaceus ) [ 46 ], and tilapia ( Oreochromis niloticus ) The study of niloticus [ 47 ] showed that feed addition of Bacillus subtilis could increase the activity of LZM in aquatic animals. In this experiment, the activity of lysozyme (LZM) in the blood of the FC8 group significantly increased ( P < 0.05), while there was no significant difference between the liver control and the experimental groups ( P > 0.05), which was similar to the results of feeding juvenile cobia with Bacillus subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…For example, certain analyses have proven the possible role of lipopolysaccharides in protection aiding in the vaccine's efficacy. Some pathogenic fish viruses, such as infectious pancreatic necrosis virus (IPNV), infectious hematopoietic necrosis virus (IHNV), viral hemorrhagic septicemia virus (VHSV), and spring viremia of carp virus (SVCV), have inactivated vaccinations (Liu et al 2021). Inactivation can be done with various physical and chemical agents; for example, when inoculated at high concentrations with formalin-inactivated IHNV, rainbow trout were shown to be protected against deadly IHNV (Salgado-Miranda et al 2013).…”
Section: Inactivated or Killed Whole-cell Oral Vaccinesmentioning
confidence: 99%